HFE genotypes in patients with chronic pancreatitis and pancreatic adenocarcinoma - Hucl, Tomas; Kylanpää-bäck, Marja-Leena; Witt, Heiko B. G.; Künzli, Beat; Lempinen, Marko; Schneider, Alexander; Kemppainen, Esko; Löhr, J.-Matthias; Friess, Helmut; Ockenga, Johann; Rosendahl, Jonas; Schulz, Hans-Ulrich; et al. (Genetics in medicine, 2007)
Purpose: The homozygous p.C282Y variant of the HFE gene is a major risk factor for hereditary hemochromatosis, a disorder of iron metabolism resulting in progressive iron accumulation in a variety of organs including the pancreas. Heterozygosity of p.C282Y and p.H63D may increase susceptibility to chronic liver and pancreatic disease. This study determines the frequencies of p.C282Y and p.H63D alterations in patients with chronic pancreatitis and pancreatic adenocarcinoma.